AUDIT INTERNAL PERSEDIAAN BARANG DAGANG DAN PENJUALAN TERHADAP PENGENDALIAN INTERNAL PELAPORAN KEUANGAN PADA PT. CAHAYA SAKTI MANDIRI - R Taufik Hidayat; Dwi Ayu Widyastuti (Jurnal Inovasi Penelitian, 2022)
This study aims to find out how much the difference in merchandise inventory will have an influence on the company's financial reporting, to find out how much the difference in sales will have an effect on the company's financial reporting, and to find out what improvements the company can make in improving the inventory control system of merchandise and sales. . The data analysis method used in the preparation of the research is qualitative analysis and descriptive analysis with data collection methods used, namely library research, as well as field research for the development of library methods. Based on the research, the results of the substantive audit of merchandise inventory in 2019, there is a difference of Rp. 18,952,000 or an increase of 2.7% from the initial balance of Rp. 689,164,210 so that the balance after the audit is Rp. 708.116.210. Meanwhile, in 2020, the audit results have a difference of Rp. 8,544,000 or an increase of 0.8% from the initial balance of Rp. 1,032,386,547 so that the balance after the audit is Rp. 1,040,930,547. The results of the substantive audit of sales in 2019, there is a difference of Rp. 24,500,000 or 0.8% of the initial balance of Rp. 2,970,823,610 so that the balance after the audit has increased to Rp. 2,995,323,610. Meanwhile, in 2020, the difference in audit results is Rp. 9,000,000 or 0.2% of the initial balance of Rp. 3,062,704,753 increased to Rp. 3,071,704,753. It is hoped that PT. Cahaya Sakti Mandiri can make improvements to improve the control and supervision of merchandise inventory and sales and present financial reports from audits conducted by researchers so that the fairness of reported earnings will be more valid.